(untitled) (Perner’s Contacts, 2014)
The paper deals with the evaluation of transport service by public bus transport in the rural territories in the district of Nitra by using the selected variables. The first and basic factor was the number of inhabitants according to which were municipalities divided into particular size groups. The mentioned evaluation run on the basis of geographical and transport indicators that should prove a hypothesis that the level of transport service increases proportionally with the number of inhabitants of the municipality, its localization within the district and relations with the district town that represents the centre of the region.